Effect Of Demographics On Customer Buying Behavior In Malls Relative To Standalone Outlets (Journal of Pharmaceutical Negative Results, 2023)
One of India's rising industries has been retail. The number of malls in India is projected to increase due to the country's retail expansion.. The present paper tries to understand the effect of demographics on shopping behavior of the customers’. The objective is to examine if the customers’ preference for mall vis-à-vis standalone store outlets and related parameters are being affected by the demographic profile of the respondents. The information was gathered from 500 consumers in the Punjabi cities of Ludhiana, Amritsar, Jalandhar, Mohali, Patiala, and Bathinda using a self-structured questionnaire. For the investigation, the cluster convenience sampling approach was adopted. The emerging retail formats considered in the present study are –malls and Standalone stores. The chi square is used as a statistical tool to test association among demographics and parameters of customer shopping. The findings of the paper reveals that Age, Education, Profession and Family size of shoppers are the variables which remained significant for most of the times and drive the choice of stores. The report also shows that customers favour malls for clothing purchases and standalone businesses for food and groceries.